Coating-free weather-resistant bridge steel with yield strength of 500 MPa and preparation method thereof

By optimizing the chemical composition and preparation process of bridge steel, a coating-free weather-resistant bridge steel with a yield strength of 500MPa was developed, which solved the problem that bridge steel cannot be used without coating in acidic pollution environments, and achieved good corrosion resistance and strength Resilience reduces maintenance costs and meets the GB714-2015 standard.

CN119287282APending Publication Date: 2025-01-10HUNAN VALIN LIANYUAN IRON & STEEL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411190890.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing bridge steel cannot be used without coating in acidic polluted atmospheric environments, and the maintenance costs are high in severely polluted areas.

Method used

By optimizing the chemical element composition ratio and preparation process, a coating-free weather-resistant bridge steel with a yield strength of 500MPa is developed, including specific contents of carbon, silicon, manganese, niobium, titanium, chromium, nickel, copper, molybdenum, and acid-soluble aluminum. , antimony and other elements, and adopt smelting, LF refining, RH refining, continuous casting, rolling and laminar flow cooling and other processes to form bainite and ferrite composite structures to improve the corrosion resistance and toughness of steel.

Benefits of technology

In an acid-polluted atmospheric environment, the use of bridge steel is achieved without coating, reducing maintenance costs, and improving the yield strength, tensile strength and impact performance of the steel, meeting the GB714-2015 standard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287282A_ABST
    Figure CN119287282A_ABST
Patent Text Reader

Abstract

The invention provides coating-free weather-resistant bridge steel with yield strength of 500 MPa and a preparation method thereof. The bridge steel comprises the following components in percentage by weight: 0.05 to 0.09 percent of carbon, 0.2 to 0.35 percent of silicon, 1.3 to 1.5 percent of manganese, less than or equal to 0.015 percent of sulfur, 0.01 to 0.018 percent of phosphorus, 0.020 to 0.050 percent of niobium, 0.01 to 0.035 percent of titanium, 0.45 to 0.5 percent of chromium, 0.3 to 0.4 percent of nickel, 0.3 to 0.35 percent of copper, 0.1 to 0.25 percent of molybdenum, 0.02 to 0.05 percent of acid-soluble aluminum, 0.03 to 0.05 percent of antimony and the balance of Fe. According to the invention, Rel is 530-580 MPa, Rm is 660-720 MPa, A is greater than 22%, and KV2 type impact energy at-40 DEG C is greater than 220 J. And the corrosion rate is below 0.30 g / (m < 2 >) in a periodic infiltration test for 144 hours.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metallurgy, and particularly relates to a coating-free weather-resistant bridge steel with a yield strength of 500 MPa and a preparation method thereof. Background Art

[0002] GB / 714-2015 raises the lower limit of the -40℃ impact value of bridge steel from 47J to 120J, and adds a guide for weathering and atmospheric corrosion resistance of weather-resistant bridge steel. The latest bridge steel used in China is the Yarlung Zangbo River Bridge on the Sichuan-Tibet Railway, whose steel is 420MPa grade weathering steel. In terms of corrosion protection, the horizontal part of the bridge deck is protected by coating, but it cannot meet the requirements of free coating in an acidic polluted atmosphere. In recent years, the large span and complex service environment of railway and highway bridges have put forward clear requirements for the toughness, corrosion resistance and maintenance of steel structures of bridge steel.

[0003] "Yield Strength 500MPa Grade Low Yield Ratio Bridge Steel and Its Manufacturing Method" (Publication No. CN106811704A) provides a low yield ratio composition and process, which contains carbon: 0.05-0.10%, silicon: 0.10-0.50%, manganese: 1.20-2.0%, niobium: 0.02-0.045%, titanium: 0.005%-0.025%, chromium: 0.40-1.0%, nickel: 0.05-0.20, copper: 0.10-0.5%, molybdenum: 0.08%-0.25%, acid-soluble aluminum: 0.01%-0.050%, and the rest is iron. A lower yield ratio and good toughness are obtained, and chromium, nickel, and copper are added to improve weather resistance, but it still needs to be painted and cannot be used without painting in areas with severe pollution.

[0004] The bridge steels reported in patent publication numbers CN105331880A, CN102021495A, and CN109112392A are all weather-resistant, but all require coating before use, and are very weak in polluted atmospheric environments, increasing the maintenance cost of engineering structural parts after service.

[0005] In order to solve the problem of using bridge steel without painting in a polluted atmospheric environment, the present invention innovatively designs the component types, content ratios and corresponding preparation processes of the bridge steel. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a 500MPa-grade paint-free weather-resistant bridge steel and a preparation method thereof. The paint-free weather-resistant bridge steel has the corrosion resistance and good strength and toughness required for paint-free use in an acidic polluted atmospheric environment.

[0007] In order to meet the above performance requirements, the present invention provides a 500MPa-grade paint-free weather-resistant bridge steel with a yield strength, which includes the following chemical elements in weight percentage: carbon 0.05-0.09%, silicon 0.2-0.35%, manganese 1.3-1.5%, sulfur ≤0.015%, phosphorus 0.01-0.018%, niobium 0.020-0.050%, titanium 0.01-0.035%, chromium 0.45-0.5%, nickel 0.3-0.4%, copper 0.3-0.35%, molybdenum 0.1-0.25%, acid-soluble aluminum 0.02-0.05%, antimony 0.03-0.05%, nitrogen ≤0.00060%, oxygen ≤0.00015%, hydrogen ≤0.0015%, and the rest are Fe and impurity elements remaining in the smelting process.

[0008] Furthermore, the yield strength 500MPa grade paint-free weather-resistant bridge steel of the present invention includes the following chemical elements in weight percentage: carbon 0.055-0.075%, silicon 0.20-0.30%, manganese 1.35-1.45%, sulfur ≤0.001%, phosphorus 0.01-0.012%, niobium 0.025-0.035%, titanium 0.02-0.030%, chromium 0.45-0.5%, nickel 0.3-0.4%, copper 0.3-0.35%, molybdenum 0.1-0.20%, acid-soluble aluminum 0.025-0.035%, antimony 0.03-0.05%, nitrogen ≤0.00060%, oxygen ≤0.0015%, hydrogen ≤0.00015%, and the rest are Fe and impurity elements remaining in the smelting process.

[0009] The structure of the steel plate of the present invention is a composite structure of bainite and ferrite.

[0010] The steel plate of the present invention has a yield strength greater than 530 MPa, a tensile strength greater than 660 MPa, an impact energy greater than 220 J at -40°C, and a corrosion weight loss less than 0.002 g / (m 2 h).

[0011] In the present invention:

[0012] Carbon: Low carbon content design can significantly increase the phase transformation temperature and is conducive to the formation of acicular ferrite. Low carbon design can reduce component segregation, ensure the uniformity of the organization, and improve corrosion resistance and welding performance. A certain content of carbon can ensure the precipitation of the second phase of carbide and the strength of the steel plate. The carbon content is controlled at 0.05-0.09%, preferably 0.055-0.075%.

[0013] Silicon: Silicon can be deoxidized during the smelting process, but too high a content of silicon will affect weldability and toughness. The content of silicon is controlled at 0.2-0.35%, preferably 0.2-0.3%.

[0014] Manganese: High manganese is beneficial to refine the bainite structure and can improve both strength and toughness. Its content is controlled at 1.3-1.5%, preferably 1.35-1.45%.

[0015] Sulfur: Sulfur easily forms MnS inclusions in steel, which are harmful to impact toughness, corrosion resistance and welding performance, so its content is ≤0.015%, preferably ≤0.001%.

[0016] Phosphorus: Too high phosphorus will cause grain boundary segregation and increase the brittleness of steel. A small amount of phosphorus can improve the weather resistance of steel. The phosphorus content is controlled at 0.01-0.018%, preferably 0.01-0.12%.

[0017] Niobium: Niobium is a carbide-forming element. Niobium carbide can inhibit the coarsening of austenite grains and obtain fine grain structure. Niobium carbide can also form a second phase reinforcement to improve strength without damaging toughness. The amount of niobium used is 0.020-0.050%, preferably 0.025-0.035%.

[0018] Titanium: During the continuous casting solidification process, titanium combines with nitrogen to form TiN, which reduces the effect of nitrogen on boron. The presence of TiN can inhibit the coarsening of grains in the welding heat affected zone. The dosage is controlled at 0.020-0.050%, preferably 0.025-0.035%.

[0019] Acid-soluble aluminum: Aluminum and a small amount of boron are beneficial to the formation of acicular ferrite, but too much aluminum will damage the toughness of the steel. The content of aluminum is controlled at 0.02-0.05%, preferably 0.025-0.035%.

[0020] Chromium: A chromium content greater than 0.2% can improve corrosion resistance, while enhancing the liquid permeability of steel and promoting the formation of acicular ferrite. The chromium content is controlled at 0.45-0.5% to ensure the combination of corrosion resistance and toughness.

[0021] Copper: Adding a certain amount of copper can form Cu2Sb precipitation phase. Sb will form a denser Sb2O5 after contacting the medium later, forming a dense passivation film, inhibiting the segregation of Sb elements at the grain boundaries, and improving the brittleness of grain boundaries. Adding 0.3-0.35% copper can increase the corrosion resistance.

[0022] Nickel: 0.3-0.4% can enhance the corrosion resistance of the steel matrix and reduce the copper brittleness of copper-containing steel.

[0023] Molybdenum: Mo significantly promotes bainite transformation and reduces the bainite transformation point Bs, which is beneficial to the refinement of bainite ferrite and improves the yield strength of steel, but also improves the yield strength ratio of steel. The dosage is controlled at about 0.1-0.25%.

[0024] Antimony: Antimony is the chemical element that has the most significant effect in improving the corrosion resistance of steel in an acidic environment. For acid rain conditions caused by severe industrial pollution, Sb significantly improves the corrosion resistance of steel. However, Sb is an element that has an adverse effect on the strength, toughness, plasticity and weldability of steel. Sb added to the metal surface can form Sb2O5 in the corrosive medium, which has higher stability than the steel matrix and is beneficial to prevent the metal matrix from being further corroded by the corrosive medium. In the present invention, the antimony content is controlled at 0.03-0.05%, which has good corrosion resistance and does not damage strength and toughness.

[0025] Gaseous elements such as nitrogen, oxygen, and hydrogen are extremely detrimental to the toughness of steel and should be strictly controlled: nitrogen ≤ 0.00060%, oxygen ≤ 0.00015%, and hydrogen ≤ 0.0015%.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] In view of the diverse environmental characteristics of my country's cross-regional hot and humid, dry, atmospheric and industrial pollution, on the basis of adding traditional chromium, nickel, molybdenum and copper to improve weather resistance, trace antimony elements are added, the ratio of each element is optimized and the preparation process is designed to match the composition. Bridge steel that can be used completely without painting in complex climate environments is prepared, and has excellent mechanical properties.

[0028] The method for preparing the 500MPa-grade coating-free weather-resistant bridge steel of the present invention comprises smelting, LF refining, RH refining, continuous casting, slab stack cooling, rolling, laminar cooling, and steel plate coiling. The key control points are:

[0029] KR desulfurization is performed as a pre-treatment: the molten iron can enter the furnace only when the sulfur content is reduced to below 0.010%.

[0030] Converter smelting: After converter smelting, argon is blown through the ladle, and the terminal temperature of the argon station is controlled to be greater than 1535℃.

[0031] LF refining: the inlet temperature is greater than 1522℃, the outlet temperature of LF is 1585-1620℃, the refining time is 40-45 minutes, the furnace is refined and the composition is fine-tuned to the target composition, the molten steel temperature is greater than 1538℃ and transferred to RH for vacuum treatment.

[0032] RH vacuum treatment: vacuum degree requirement ≤67MPa, RH cycle time 22-30min.

[0033] Continuous casting: The continuous casting speed is controlled at 0.9-1.1m / min, and the casting adopts the light pressure mode.

[0034] The ingot is rolled after being cooled to room temperature. The rolling process includes: heating the ingot in the furnace, entering the single stand for 5 rough rolling passes, and then rolling in the finishing mill for 7 passes. After rolling, the ingot enters the laminar cooling system for tissue control.

[0035] The slab heating temperature is 1200-1220℃, the required heating time is 150-250min, and the solution time is 30min.

[0036] The thermomechanical controlled rolling and controlled cooling process during the rolling process is as follows: the starting temperature of rough rolling is 1150-1180℃, the final rolling temperature of rough rolling is 1000-1080℃, the starting temperature of finishing rolling is 980-1060℃, the final rolling of finishing rolling is 830-880℃, followed by laminar cooling at a cooling rate of 20-30℃ / s, and finally cooling to 500-560℃ for coiling.

[0037] Hot rolling is based on metal deformation, phase change and other processes. Under the specified deformation and temperature conditions, solid solution strengthening, precipitation strengthening, dislocation strengthening, refinement strengthening and other hardening measures are completed to obtain steel plates with excellent comprehensive performance. Reduce the use of precious alloys, reduce manufacturing costs, and make full use of the rolling and cooling capacity of the continuous rolling unit. Paint-free bridge steel is produced by controlled rolling and accelerated cooling. The best effect is achieved through deformation recrystallization in the high-temperature austenite zone, deformation in the low-temperature austenite non-recrystallization zone, and accelerated cooling after rolling.

[0038] In the present invention, at a cooling rate greater than 20°C / s, the bainite start transformation temperature is 590°C and the bainite transformation end temperature is 420°C. By adopting an ultra-fast cooling process, a small amount of acicular ferrite is produced along the austenite grain boundary or in the austenite grain in advance, dividing the austenite grains into a number of small spaces. When cooled to the bainite region, the transformation speed is very fast, and the divided spaces limit the growth of the lath bundles, thereby refining the structure.

[0039] The properties of the paint-free bridge steel produced by the composition and supporting process of the present invention are as follows: yield strength Rel: 530-580MPa, tensile strength Rm: 660-720MPa, yield strength ratio Rel / Rm≤0.85, elongation greater than 22%, -40℃ KV2 type impact energy greater than 220J. The corrosion rate of the 144-hour 0.01mol / L sodium bisulfite cycle immersion test is 0.30g / (m 2 )the following. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The metallographic structure diagram of the 10 mm thick paint-free bridge steel plate of Example 1;

[0041] Figure 2 The metallographic structure diagram of the 20 mm thick paint-free bridge steel plate of Example 2;

[0042] Figure 3 Flow chart of the preparation process for paint-free bridge steel. DETAILED DESCRIPTION

[0043] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, they are described in detail below in conjunction with specific embodiments.

[0044] The following examples and comparative examples are used to describe the implementation process of the present invention in detail.

[0045] like Figure 3 As shown, the bridge steel of the present invention is produced by the following preparation process, which includes the following steps: smelting, LF refining, RH refining, continuous casting, slab stack cooling, rolling, laminar cooling, steel plate coiling, cross-cutting, flattening, inspection and warehousing.

[0046] The molten iron is desulfurized by KR (sulfur content is removed to less than 0.010%) and then smelted in a 210-ton converter, then argon blowing in a ladle (the terminal temperature of the argon station is controlled to be greater than 1535°C), LF furnace refining (entry temperature is greater than 1522°C, LF exit temperature is 1585-1620°C, and refining time is 40-45 minutes), RH vacuum treatment (vacuum degree requirement is ≤67MPa, RH cycle time is 22-30min), and continuous casting into 230mm slabs (continuous casting speed is controlled at 0.9-1.1m / min, and the slabs are cast in a light pressure mode). The slabs are pile-cooled for 48 hours, reheated, and rough-rolled for 5 times, and then thermomechanically controlled rolling and controlled cooling are carried out by a 7-stand 2250 continuous rolling unit. The thickness specifications of the hot-rolled coils are 10mm and 20mm. The slab heating temperature is 1200-1220°C, the required heating time is 150-250min, and the solution time is 30min. The thermomechanical controlled rolling and cooling process during the rolling process is as follows: the starting temperature of rough rolling is 1150-1180℃, the final rolling temperature of rough rolling is 1080-1000℃, the starting temperature of finishing rolling is 1060-980℃, the final rolling of finishing rolling is 880-830℃, followed by laminar cooling at a cooling rate of 20-30℃ / s, and finally cooling to 560-500℃ for coiling.

[0047] The composition of the paint-free bridge steel of the present invention is shown in Table 1; and the remaining elements in Examples 1 and 2 and the comparative example are Fe, and in Examples 1 and 2, nitrogen ≤0.00060%, oxygen ≤0.00015%, and hydrogen ≤0.0015%.

[0048] The controlled rolling and controlled cooling process parameters are shown in Table 2, the mechanical properties are shown in Table 3, the cyclic infiltration test results are shown in Table 4, and the comparison steel grade is Q450NQR1.

[0049] Table 1 Chemical composition of weathering bridge steel examples and comparative examples (%)

[0050] serial number C Si Mn S P Nb Ti Cr Ni Cu Mo Als Sb Example 1 0.063 0.23 1.40 0.0008 0.015 0.033 0.025 0.48 0.33 0.33 0.15 0.034 0.038 Example 2 0.065 0.26 1.42 0.0008 0.012 0.034 0.018 0.46 0.35 0.33 0.13 0.028 0.045 Example 3 0.050 0.20 1.30 0.0008 0.010 0.020 0.010 0.45 0.30 0.30 0.10 0.020 0.030 Example 4 0.090 0.35 1.50 0.0008 0.018 0.050 0.035 0.50 0.40 0.35 0.25 0.050 0.050 Example 5 0.055 0.20 1.35 0.0008 0.010 0.025 0.020 0.45 0.30 0.30 0.10 0.025 0.030 Example 6 0.075 0.30 1.45 0.0008 0.012 0.035 0.030 0.50 0.40 0.35 0.20 0.035 0.050 Comparative Example 1 0.063 0.23 1.40 0.0008 0.015 0.033 0.025 0.42 0.33 0.33 0.15 0.034 0.038 Comparative Example 2 0.065 0.26 1.42 0.0008 0.012 0.034 0.018 0.46 0.27 0.33 0.13 0.028 0.045 Comparative Example 3 0.050 0.20 1.30 0.0008 0.010 0.020 0.010 0.45 0.30 0.28 0.10 0.020 0.030 Comparative Example 4 0.090 0.35 1.50 0.0008 0.018 0.050 0.035 0.50 0.40 0.35 0.07 0.050 0.050 Comparative Example 5 0.055 0.20 1.35 0.0012 0.010 0.025 0.020 0.45 0.30 0.30 0.10 0.025 0.030 Comparative Example 6 0.075 0.30 1.45 0.0008 0.012 0.035 0.030 0.50 0.40 0.35 0.20 0.035 0.029 Q450NQR1 0.070 0.35 1.10 0.001 0.015 0.028 0.020 0.65 0.14 0.26 0.09 0.030 Not added

[0051] The specific heating process of the paint-free bridge steel used in each embodiment is 1200-1220℃, the heating time in the furnace is 150-250min, the first stage is rough rolling, the starting rolling temperature is 1150-1180℃, and the final rolling temperature is 1000-1080℃; the second stage is finishing rolling, the starting rolling temperature is 980-1060℃, the final rolling temperature is 830-880℃, and after rolling, the steel strip is laminarly cooled by ACC controlled cooling, the cooling rate is 20-30℃ / s, and the coiling temperature is 500-560℃. The metallographic organization diagrams of the steel plates of Example 1 and Example 2 are shown respectively. Figure 1 and 2 shown.

[0052] Table 2 Specific rolling process parameters of the embodiments and comparative examples

[0053]

[0054] Table 3 Specific mechanical properties of the embodiments and comparative examples

[0055]

[0056] The yield strength of the paint-free bridge steel involved in the embodiments of the present invention meets the requirements of being greater than 530MPa, and the tensile strength is greater than 660MPa. The elongation after fracture is greater than 22%, the yield strength ratio is less than 0.85, and the impact energy at -40°C is greater than 220J. All indicators meet the requirements of GB714-2015, and are more than sufficient. The mechanical properties of comparative examples 1-6 are insufficient. In addition to the influence of the element dosage, it may be that the cooling rate is too low, which changes the structure in the alloy and affects the mechanical properties of the steel.

[0057] The results of immersion in an acidic environment with a pH value of 4-5 and a 0.01 mol / L NaHSO3 solution are shown in Table 4.

[0058] Table 4 Cycle immersion test results

[0059]

[0060]

[0061] From the results of the periodic infiltration test in Table 4, the present invention adjusts the dosage of any key element, which has a huge impact on the corrosion resistance. The reason is that the present invention uses traditional chromium, nickel, molybdenum, copper and other elements to improve weather resistance, and also adds trace antimony elements. Each element plays an important role in the corrosion resistance of the metal, and the interaction between the elements affects the corrosion resistance. In particular, some elements can be combined with each other, such as the formation of a dense protective film Cu2Sb between copper and antimony, and the dosage of S element has an important influence on the corrosion resistance. Therefore, the present invention needs to strictly control the dosage of S element. In summary, adjusting the dosage of the constituent elements of the present invention within a suitable range can achieve good corrosion resistance while ensuring the mechanical properties of the steel, and can be used to manufacture new bridge steel.

[0062] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A coating-free weather-resistant bridge steel with a yield strength of 500 MPa, characterized in that: The chemical elements include the following weight percentages: carbon 0.05-0.09%, silicon 0.2-0.35%, manganese 1.3-1.5%, sulfur ≤0.015%, phosphorus 0.01-0.018%, niobium 0.020-0.050%, titanium 0.01-0.035%, chromium 0.45-0.5%, nickel 0.3-0.4%, copper 0.3-0.35%, molybdenum 0.1-0.25%, acid-soluble aluminum 0.02-0.05%, antimony 0.03-0.05%, nitrogen ≤0.00060%, oxygen ≤0.00015%, hydrogen ≤0.0015%, and the rest are Fe and impurity elements remaining in the smelting process.

2. The coating-free weather-resistant bridge steel with a yield strength of 500 MPa as claimed in claim 1, characterized in that: The chemical elements include the following weight percentages: carbon 0.055-0.075%, silicon 0.20-0.30%, manganese 1.35-1.45%, sulfur ≤0.001%, phosphorus 0.01-0.012%, niobium 0.025-0.035%, titanium 0.02-0.030%, chromium 0.45-0.5%, nickel 0.3-0.4%, copper 0.3-0.35%, molybdenum 0.1-0.20%, acid-soluble aluminum 0.025-0.035%, antimony 0.03-0.05%, nitrogen ≤0.00060%, oxygen ≤0.0015%, hydrogen ≤0.00015%, and the rest are Fe and impurity elements remaining in the smelting process.

3. The method for preparing the 500MPa-grade coating-free weathering bridge steel according to claim 1 or 2, comprising smelting, LF refining, RH refining, continuous casting, slab stack cooling, rolling, laminar cooling, and steel plate coiling, wherein: The rolling process includes 5 rough rolling passes and 7 finish rolling passes. The starting temperature of rough rolling is 1150-1180°C, the final temperature of rough rolling is 1000-1080°C, the starting temperature of finish rolling is 980-1060°C, and the final temperature of finish rolling is 830-880°C.

4. The preparation method according to claim 3, characterized in that: It also includes pre-treatment, namely KR desulfurization: the sulfur content is reduced to below 0.010%.

5. The preparation method according to claim 3, characterized in that: After smelting, argon is blown through the ladle, and the terminal temperature of the argon station is controlled to be greater than 1535℃.

6. The preparation method according to claim 3, characterized in that: LF refining: the inlet temperature is greater than 1522℃, the outlet temperature of LF is 1585-1620℃, the refining time is 40-45 minutes, the molten steel temperature is greater than 1538℃ and is transferred to RH for vacuum treatment.

7. The preparation method according to claim 3, characterized in that: RH vacuum treatment: vacuum degree requirement ≤67MPa, RH cycle time 22-30min.

8. The preparation method according to claim 3, characterized in that: The continuous casting speed is controlled at 0.9-1.1m / min, and the casting adopts the light pressure mode.

9. The preparation method according to claim 3, characterized in that: The ingot is rolled after being cooled to room temperature. Before rolling, the ingot needs to be heated in a furnace. The heating temperature of the ingot is 1200-1220°C, the heating time is required to be 150-250 minutes, and the solution time is 30 minutes.

10. The preparation method according to claim 3, characterized in that: After rolling, the steel is cooled by laminar flow at a cooling rate of 20-30°C / s and finally cooled to 500-560°C for coiling.

Citation Information

Patent Citations

  • 420 MPa weatherproof bridge steel with high ductility and method for manufacturing hot rolled coil of 420 MPa weatherproof bridge steel with high ductility

    CN102021495A

  • High-strength weather-proof bridge steel and preparation method thereof

    CN105331880A

  • Low-yield-ratio bridge steel with yield strength being 500 MPa and manufacturing method thereof

    CN106811704A

  • TMCP type high strength and toughness high fatigue resistance weather-proof bridge steel plate, and preparation method thereof

    CN109112392A